The response of concave singly curved fibre reinforced moulded sandwich and laminated composite panels to blast loading - Ghoor, Ismail B (Blast Impact and Survivability Research Unit, 2018)
Composite materials are increasingly being used in a wide range of structural applications. These applications range from bicycle frames and building facades to hulls of marine ships. Their popularity is due to the high specific strength and stiffness properties, corrosion resistance, and the ability to tailor their properties to a required application. With the increasing use of composites, there is a need to better understand the material and damage behaviour of these structures. In recent years, the increased frequency of wars and terror attacks have prompted investigations into composite failure processes resulting from air-blast. Most of the research has been focused on flat panels, whereas there is relatively little on curved structures. This dissertation reports on the effect of air-blast loading on concave, singly curved fibre reinforced sandwich and composite panels. Sandwich panels and equivalent mass glass fibre laminates were manufactured and tested. Three types of curvature namely a flat panel (with infinite curvature), a curvature of 1000 mm radius and a curvature of 500 mm radius were produced, to determine the influence of curvature on panel response. The laminates were made from 16 layers of 400 g/m² plain weave glass fibre infused with Prime 20 LV epoxy resin. The sandwich panels consisted of a 15 mm thick Airex C70:75 core sandwiched between the 12 layers of 400 g/m² plain weave glass fibre and infused with Prime 20 LV epoxy resin. This arrangement produced a balanced sandwich panel with 6 layers of glass fibre on the front and back respectively. For all panels, vacuum infusion was used to manufacture in a single shot process. Mechanical properties of samples were tested for consistency in manufacturing. It was found that mechanical properties of the samples tested were consistent with low standard deviations on tensile and flexural strength. The panels were tested in the blast chamber flat the University of Cape Town. Blast specimens were clamped onto a pendulum to facilitate impulse measurement. Discs of plastic explosive, with charge masses ranging from 10 g to 25 g, were detonated. After blast testing, a post-mortem analysis of the damaged panels was conducted. Post-mortem analysis revealed that the failure progression was the same irrespective of curvature for both the sandwich panels and the laminates. Sandwich panels exhibited the following failure progression: delamination, matrix failure, core crushing, core shear, core fragmentation, core penetration and fibre fracture. The laminates displayed the following progression: delamination, matrix failure and fibre fracture. Curved panels exhibited failure initiation at lower charge masses than the flat panels. As the curvature increased, the failure modes initiated at lower charge masses. For example, as the charge mass was increased to 12.5 g the front face sheets of the flat and the 1000 mm radius sandwich panels exhibited fibre fracture, but the 500 mm radius sandwich panel exhibited fibre fracture and rupture through the thickness of the front face sheet. The 500 mm radius laminate exhibited front face failure earlier (15 g) than the 1000 mm radius (22.5 g) and flat panel (20 g). Curved laminates exhibited a favoured delamination pattern along the curved edges of the panel for both 1000 mm and 500 mm radii laminates. As the curvature increased, more delamination was evident on the curved edges. The curved panels displayed more severe damage than flat panels at identical charge masses. Curved sandwich panels experienced through thickness rupture at 20 g charge mass whereas the curved laminates did not exhibit rupture at 25 g charge mass. The flat laminates were the most blast resistant, showing no through-thickness penetration at 25 g (the highest charge mass tested) and initiated failure modes at higher charge masses when compared to the other configurations.